Mechanisms of Anergic Inflammatory Response in Nasopharyngeal Carcinoma Cells Despite Ubiquitous Constitutive NF-κB Activation - Zhou, Xiaoying; Matskova, Liudmila; Zheng, Shixing; Wang, Xiaoxia; Wang, Yifang; Xiao, Xue; Mo, Yingxi; Wölke, Marleen; Li, Limei; Zheng, Qian; Huang, Guangwu; Zhang, Zhe; et al. (Frontiers in Cell and Developmental Biology, 2022)
Commensal microbes cross-talk with their colonized mucosa. We show that microbes and their cell wall components induce an inflammatory response in cultured human mucosal cells derived from the non-malignant nasopharyngeal epithelium (NNE) cells in vitro. NNE cells show significant induction of NF-κB with nuclear shuttling and inflammatory gene response when exposed to gram-positive bacteria (streptococci) or peptidoglycan (PGN), a component of the gram-positive bacterial cell wall. This response is abrogated in nasopharyngeal carcinoma (NPC)-derived cell lines. The inflammatory response induced by NF-κB signaling was blocked at two levels in the tumor-derived cells. We found that NF-κB was largely trapped in lipid droplets (LDs) in the cytoplasm of the NPC-derived cells while the increased expression of lysine-specific histone demethylase 1 (LSD1, a repressive nuclear factor) reduces the response mediated by remaining NF-κB at the promoters responding to inflammatory stimuli. This refractory response in NPC cells might be a consequence of the long-term exposure to microbes in vivo during the carcinogenic progression. It may contribute to the decreased anti-tumor immune responses in NPC, among others despite heavy T-helper cell infiltration, and thus facilitate tumor progression.